Islamic Higher Education Institutional Change: Leader's Motivation and Vision - Mochamad Iskarim; Sutrisno; Tasman Hamami; Muhammad Zubair Khan (Edukasia Islamika : Jurnal Pendidikan Islam, 2021)
This paper discusses the motivation and vision of state Islamic higher education leaders in their attempt to improve higher education quality after the institutional change. This is a field descriptive qualitative study which is conducted in IAIN Purwokerto and IAIN Pekalongan. The data collection is done using documentation and interview method; the data is analyzed using an interactive analysis model which covers steps of data collection, data reduction, data presentation, and verification/conclusion. The results of the study are as follows: (1) the institutional change which is frequently experienced by state Islamic higher education institutions is considered as the starting point of the effort to increase academic and institutional quality. This institutional change must be followed by well-prepared quality management of higher education institutions; planned, executed, monitored, and evaluated synergically; (2) the leader’s motivation and vision serve as an important aspect in the effort to improve the institutional quality. The motivation and vision must be elaborated into real and calculated actions, as well as supported by transformational leadership; and (3) the accreditation and fulfillment of facilities and infrastructure of higher education is a tool the final objective of which is the establishment of true quality, namely quality culture displayed by the academic community. As a recommendation, the motivation and vision of higher education leaders should focus on improving internal institutions, improving education services and public accountability, and the relevance of education to the future needs of the new generation in the future.